Comparative analyses of reproductive activity in Schizodon knerii (Steindachner, 1875) (Characiformes: Anostomidae) in three sections of the São Francisco River basin. (4th August 2017) - de Esquivel Dias Brandão, L.; Virtude do Nascimento, A.; Marcon, L.; Enemir dos Santos, J.; Biana Santiago, K.; Rizzo, E.; Bazzoli, N.
Summary: This paper aims to establish possible changes in the main reproductive parameters of the so‐called piau‐branco, Schizodon knerii, in three sections of the São Francisco River basin. Fish ( n  = 388) were captured quarterly between May 2012 and April 2013 from three sections of the São Francisco River (SFR): section 1 = Três Marias Reservoir (TMR), a lentic environment; section 2 = SFR, the first 34 km downstream of TMR, a lotic environment in which the temperature, oxygen levels, and flow are not suitable for reproduction; section 3 = SFR, 34–54 km downstream from TMR after the confluence with the Abaeté River, a lotic environment in which temperature, oxygen levels and flow are suitable for reproduction. In section 2, females and males showed lower values of total length and body weight in relation to fish from sections 1 and 3. The reproductive mode of S. knerii in sections 1 and 3 exhibited a prolonged reproductive period, parceled spawning, and a reproductive peak from January to March. In section 2, neither spawning females or spermiated males were captured, probably due to the fact that this section receives cold water with low oxygen levels from the hypolimium of the dam that presents thermal stratification in the summer. This study showed in section 2, immediately downstream of the Três Marias Reservoir, that S. knerii does not reproduce successfully.